The role of innovations in fostering economic growth: an empirical analysis for selected CEE countries. (17th June 2019) - Lazarov, Darko; Petreski, Goce
The main aim of the paper is to investigate whether the innovation performance is a driving force to economic growth in selected CEE countries. To fulfil this goal, we use dynamic panel regression approach (system GMM), for the period 2002-2014. The innovation performance is derivate from several indicators (general expenditure on R&D, number of patents, journal articles and scientific publications, as well as royalty payments) by using principle component factor analysis. The estimated results suggest that innovation performance has positive and significant influence on economic growth, indicating that those countries with more efficient innovation system have experienced higher economic growth. Moreover, the paper found the higher magnitude in the impact of innovation performance on economic growth in new EU member state economies, compare to less developed non-EU countries. This indicates that innovations become more important growth determent how the countries are catching-up to developed countries.